The Effect of Pineapple Leaf Fiber Addition to Mechanical and Thermal Characteristics of Sago Starch Based Biofoam with Thermopressing Method - Rozanna Dewi; Novi Sylvia; Zulnazri Zulnazri; Medyan Riza (Indonesian Journal of Chemical Analysis (IJCA), 2023)
Biofoam can be used as an alternative packaging to Styrofoam. Biofoam made from starch and cellulose fibers has biodegradable properties. In this study used pineapple leaf fiber as an additive to strenghen on mechanical properties of biofoam. The research method consists of several stages, cooking pineapple leaf fiber, biofoam preparation, and testing phase on the resulting biofoam. The mechanical characteristics test of biofoam is a tensile strength test of 1.66-2.86 Mpa. Compound composition test through Fourier Transform Infrared Spectroscopy (FTIR) is hydrophilic which binds to water so that it is easily degraded by soil, thermal characteristics with DSC thermogram test of pineapple leaf fiber biofoam sample 15 gr shows at a temperature of 98.04 °C occurs peak thermogram showing physical changes. TGA analysis showed that biofoam has good thermal stability. In the morphology of biofoam visible white lumps and grooves on the surface that shows the solubility is not too perfect due to the influence of stirring time.